Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]m^2+2m-48=-6 \\ \\ m^2+2m-48+6=0\\ \\m^2+2m-42=0\\ \\a=1, \ b= 2, \ c= -42 \\ \\\Delta = b^{2}-4ac = 2^{2}-4*1*(-42)= 4+168 =172 \\\\\sqrt{\Delta }=\sqrt{172} =\sqrt{4*43}=2\sqrt{43}\\ \\x_{1}=\frac{-b-\sqrt{\Delta }}{2a} =\frac{-2-2\sqrt{43}}{2}=\frac{2(-1-\sqrt{43})}{2}= -1-\sqrt{43} \\ \\x_{2}=\frac{-b+\sqrt{\Delta }}{2a} = \frac{-2+2\sqrt{43}}{2}=\frac{ 2(-1+\sqrt{43})}{2}= -1+\sqrt{43}[/tex]
[tex]m^2+2m-48=-6\\\\m^2+2m\cdot1+1^2-1^2=-6+48\\\\(m+1)^2-1=42\\\\(m+1)^2=42+1\\\\(m+1)^2=43\iff m+1=-\sqrt{43}\ \vee\ m+1=\sqrt{43}\\\\m=-1-\sqrt{43}\ \vee\ m=-1+\sqrt{43}[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.